Endoscopic selective biliary stenting and reintervention using metal stents with a slim delivery system in a patient with complexly altered digestive anatomy. (20th October 2021) - Nishikawa, Takao; Kamiya, Junichiro; Takeuchi, Dan
Abstract : Nishikawa and colleagues describe a case of endoscopic multiple stenting for malignant biliary stenosis in a patient with complexly altered digestive anatomy following hepaticojejunostomy with Roux‐en‐Y anastomosis and gastrojejunostomy with Braun enterostomy. Furthermore, reintervention for malignant stenosis extending from the intrahepatic bile duct to the intestinal tract was successfully completed.